1979
DOI: 10.1093/ageing/8.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic Studies in the Management of Urinary Incontinence in the Elderly

Abstract: An outline is given of simple urodynamic investigations applicable to elderly subjects. The type of patient presenting primarily to geriatric departments with urinary incontinence, whose management is aided by such studies, is described under various clinical groupings. The requirement for urodynamic studies and the best means of providing these for the elderly patient is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

1984
1984
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 4 publications
1
12
1
Order By: Relevance
“…There is a major discrepancy between the types of urinary incontinence obtained from history and physical examination and that of the urodynamic evaluation, a finding supported by previous investigators 9–13 . The major differences are experienced mostly in those patients clinically determined to be mixed (urge and stress) or pure urge urinary incontinence.…”
Section: Discussionmentioning
confidence: 81%
“…There is a major discrepancy between the types of urinary incontinence obtained from history and physical examination and that of the urodynamic evaluation, a finding supported by previous investigators 9–13 . The major differences are experienced mostly in those patients clinically determined to be mixed (urge and stress) or pure urge urinary incontinence.…”
Section: Discussionmentioning
confidence: 81%
“…Whether or not impairments of physical function (especially mobility) and/or impaired cognitive function are primary causes of UI in most NH patients, the strong association of these impairments with UI has important implications for strategies to assess and treat UI in the NH setting. The appropriate extent of diagnostic evaluation for geriatric UI, especially with regard to urodynamic testing, is controversial 1,9–13 . Urodynamic tests can clearly identify abnormalities in lower genitourinary function that are amenable to specific types of treatment 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Most have involved young and middle‐aged women, have focused on urinary incontinence, and have attempted to correlate symptoms with lower GU tract dysfunction as defined by urodynamic testing 2 . Several studies have focused on the geriatric population 2–11 ; interpretation of many of these studies is complicated for several reasons, including: the relatively limited clinical, GU, and urodynamic findings reported; inconsistent terminology relating to urodynamic abnormalities; and potential selection biases in the study populations that cannot be ascertained from the data reported.…”
mentioning
confidence: 99%